Measurement of exhaled breath carbon monoxide in clinical practice: A study of levels in Central Pennsylvania community members. Issue 6 (25th April 2017) - Hrabovsky, Shari; Yingst, Jessica M.; Veldheer, Susan; Hammett, Erin; Foulds, Jonathan
Abstract: Background and purpose: Exhaled breath carbon monoxide (eBCO) reading is a useful tool for nurse practitioners to evaluate smoking status and other exposures to carbon monoxide (CO) to identify risk for cancer and chronic disease. This study aimed to measure one community's eBCO and identify potential environmental factors that may affect eBCO among nonsmokers. Methods: Data collected by convenience sampling at community health events included self‐reported tobacco use and potential CO exposure. Means and frequency calculations describe the sample, two‐sided t ‐tests determine differences in continuous variables, and chi‐square tests determine differences in frequencies of CO levels between nontobacco users exposed to additional CO from their environment and nontobacco users who were not. Conclusion: As expected, smokers have significantly higher mean eBCO than nonsmokers (20.1 ppm vs. 4.4 ppm, p < .001). The self‐reported nonsmokers (16.2%) had an elevated eBCO (>6 ppm), although there were no environmental factors that explained a higher eBCO. Implications for practice: Measuring eBCO provides an opportunity for the nurse practitioner to engage in a conversation about the impact of smoking and other environmental factors that contribute to eBCO and health. Keeping record of patients' smoking status and eBCO in their medical record is a valuable measure of the nurse practitioner's delivery of this care.